Kepemimpinan Etis dan Dukungan Organisasi terhadap Perilaku Kewargaan Organisasional Mahasiswa Anggota UKM di Tanjungpinang - Fani, Lastri Anggi; Randa, Fradya; Sufnirayanti (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to analyze the influence of ethical leadership and perceived organizational support on organizational citizenship behavior (OCB) among students actively involved in Student Activity Units (UKM) in Tanjungpinang. The phenomenon of low voluntary participation among students in organizational activities highlights the need to examine factors that may enhance such extra-role behaviors. A quantitative approach with a survey design was employed, and data were collected through questionnaires distributed to 120 active UKM students. The data were analyzed using multiple linear regression. The findings indicate that ethical leadership does not have a significant effect on students’ OCB. In contrast, perceived organizational support was found to have a positive and significant effect on OCB. Furthermore, when tested simultaneously, ethical leadership and perceived organizational support significantly influence OCB, with 98 percent of the variance in students’ behavior explained by these two variables, while the remaining 2 percent is explained by other factors outside the research model. These results emphasize that perceived organizational support plays a dominant role in shaping students’ OCB, while ethical leadership still serves as a complementary factor that strengthens the overall model.